E-commerce in the Asian context : selected case studies - Lafond, Renald; Sinha, Chaitali (International Development Research Centre ; Institute of Southeast Asian Studies, 2005)
E-commerce in Asia has been receiving considerable attention as a result of the proliferation of Internet connectivity and technologies in the region. In response to this trend, Canada's International Development Research Centre (IDRC) commissioned four studies to investigate the various economic, social, methodological, and security issues related to this emerging business paradigm. The scope of these reports ranges from the policy environment in Vietnam to the empowerment of rural women's artisan groups in southern India. The studies were underaken to explore the technical and socioeconomic achievements and challenges faced by e-commerce in Asia, and to better understand the lessons learned and future developments of this dynamic business model.